N-(2-Methylphenyl)maleamic acid - Gowda, B. Thimme (International Union of Crystallography, 2010)
In the title compound, C(11)H(11)NO(3), the conformation of the N—H bond is anti to the C=O bond in the amide segment, while it is syn to the ortho-methyl group in the phenyl ring. In the maleamic acid unit, the amide C=O bond is anti to the adjacent C—H bond, while the carboxyl C=O bond is syn to the adjacent C—H bond. The C=O and O—H bonds of the acid group are in the relatively rare anti position to each other. This is an obvious consequence of the intramolecular O—H⋯O hydrogen bond donated to the amide carbonyl group. The ortho-substituted phenyl ring makes a dihedral angle of 12.7 (1)° with the mean plane of the maleamic acid unit. In the crystal structure, intermolecular N—H⋯O hydrogen bonds link the molecules into zigzag chains parallel to [001]. These chains are further linked into sheet by weak π–π interactions [centroid–centroid distance = 3.425 (2) Å].